Storage Techniques of Recalcitrant Seeds: Mesua ferrea L. and Swinglea glutinosa (Blanco) Merr. - Dewi Ayu Lestari (Jurnal Perbenihan Tanaman Hutan, 2019)
Mesua ferrea L. and Swinglea glutinosa (Blanco) Merr. are two species of plants with recalcitrant seed character. Recalcitrant seed have problem with storage, because they cannot stand being stored for long periods of time. Storage method becomes indispensable in recalcitrant seeds conservation. The storage methods were using 3 treatments, namely media of storage, storage time and room of storage, analyzed by using factorial design with 2 replication. Each treatment combination was tested for seed moisture content, rate of germination and seed germination value. The results showed that the viability of M. ferrea seeds can be maintained up to 55 percent ―90 percent if they were stored for 2 months, at either room temperature or freezer temperature put in a glass jar with silica. Seeds of S. glutinosa have germination percent in a range of  83.33 percent ―93.33 percent after being stored for 1 month at room temperature, wrapped with aluminium foil, as well as stored under freezer temperature put in a glass bottle containing silica. Based on this test, both of seed species are recalcitrant because they cannot stored for long time periods.